PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA BEAT PADA DEALER CV. SUPRA JAYA MOTOR CIANJUR - Leo Nardo; Budi Prasetiyo (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Motorcycles are a favorite means of transportation that are chosen by the community, especially because the current level of congestion is very high, so that one alternative is to make it easier and smoother to reach destinations in the city. The growth of motorcycle consumers that continues to fluctuate resulting in many new entrants in various categories. This study aims to obtain data and information regarding product quality and price perceptions, and to determine the extent of their influence on purchasing decisions for Honda BEAT Motorcycles in Cianjur. This study uses quantitative methods and uses the Non-Probability Sampling technique with an incidental sampling technique approach of 72 people. The research findings found that the variable quality of the product on the Honda BEAT motorcycle can be seen that the score is 305.8. Variable price perception on the Honda BEAT motorcycle can be seen that the results are very good because it reaches a score of 304.25. Variable purchasing decisions for Honda BEAT motorcycles at CV. Supra Jaya Motor Cianjur Dealers can be seen the results are good because they reach a score of 296.4.